2018
DOI: 10.1021/acsabm.8b00266
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Aryldiazonium Grafting for the Preparation of Functional Cyclodextrin-Modified Materials

Abstract: A mild and efficient surface modification protocol for the preparation of β-cyclodextrin (βCD) modified surfaces through aryldiazonium mediated grafting is reported. Mono substituted 6-Oaminophenol-β-Cyclodextrin (amβCD) was synthesized through a three step protocol. This compound was found to form supramolecular aggregates in aqueous solutions at relatively low concentrations via cavity-directed self-assembly. Disruption of these supramolecular structures through judicious choice of solvent was found to be es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A 35 s potential step was used to reductively graft phenyl-glycosides; the total integrated charge density obtained via normalization by the exposed geometric area and associated with the generation of aryl radicals during the potential step experiments for all samples is reported in Table 1 . Results show that for both ITO and GR, the total charge is well in excess over the value required for monolayer grafting (10 −6 –10 −5 mol m −2 corresponding to 0.1–1.0 C m −2 ) [ 52 , 53 ]. Integrated charges on GR substrates were more than an order of magnitude larger than those obtained with ITO surfaces; this is likely due to the greater microroughness displayed by polished GR surfaces (rms 61 ± 16 nm) [ 14 ] compared to the ITO substrates (see below).…”
Section: Resultsmentioning
confidence: 99%
“…A 35 s potential step was used to reductively graft phenyl-glycosides; the total integrated charge density obtained via normalization by the exposed geometric area and associated with the generation of aryl radicals during the potential step experiments for all samples is reported in Table 1 . Results show that for both ITO and GR, the total charge is well in excess over the value required for monolayer grafting (10 −6 –10 −5 mol m −2 corresponding to 0.1–1.0 C m −2 ) [ 52 , 53 ]. Integrated charges on GR substrates were more than an order of magnitude larger than those obtained with ITO surfaces; this is likely due to the greater microroughness displayed by polished GR surfaces (rms 61 ± 16 nm) [ 14 ] compared to the ITO substrates (see below).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 demonstrates the surface charge and particle size of the synthesized nanocomposites. The hydrodynamic sizes and surface charges of KZ, β-CD and β-CD /KZ were already reported (Hedayati et al 2020) as the bigger hydrodynamic size related to β-CD and creation of hydrogen or weak physical bonding (Attarchi et al 2013;Hedayati et al 2020;Myles et al 2018). Further, The KZ with two active chlorine groups increased the hydrodynamic diameter of particles due to the possible interactions between KZ and β-CD and hydrolysis of KZ in alkali media according to Fig3, Reaction 1 (Reichle 1970).…”
Section: Dynamic Light Scattering (Dls)mentioning
confidence: 97%
“…Work from our group has shown that aryldiazonium cations prepared from saccharidebearing aminophenol precursors as in Figure 1 [13], can be used to spontaneously form adlayers of mono-and di-saccharides from solution in a single step. This reaction yields covalent immobilization of glycans on a range of materials including carbon [13][14][15], polymers [16,17], metals and alloys [13,18]; furthermore, it has been extended to more complex glycans that display specific binding interactions with organic substrates, such as cyclodextrins [19].…”
Section: Introductionmentioning
confidence: 99%